Regimes de interação no videoclipe: a experiência interativa de The Wilderness Downtown - Médola, Ana Sílvia Lopes; Caldas, Carlos Henrique Sabino (Programa de Estudos Pós-graduados em Comunicação e Semiótica - PUC-SP, 2015)
AbstractThis paper analyzes the videoclip within the context of media convergence, where the production resources available in different infoelectronic communication devices may actuate in the constitution process of their language, creating innovative experiences in the ways of fruition and in the realities of consumption. By being structured on the interactive relationships made possible by digital technologies of contemporary media, we intend to demonstrate how the enunciative strategies are major discourse-making mechanisms in the configuration of the new music video formats. In this perspective, we will analyze the interactive music video experience developed by director Chris Milk, The Wilderness Downtown, from the theoretical and methodological framework of sociosemiotics, especially the regimes of interaction.

ResumoO artigo analisa o videoclipe dentro do contexto de convergência midiática, em que os recursos de produção presentes nos diferentes dispositivos de comunicação infoeletrônicos agem no processo de constituição de sua linguagem, criando experiências inovadoras nos modos de fruição e nas realidades de consumo. Estruturados sobre as relações interativas possibilitadas pelas tecnologias digitais das mídias contemporâneas, pretende-se demonstrar como as estratégias enunciativas constituem um dos principais mecanismos de discursivização na configuração dos novos formatos de videoclipes. Nesta perspectiva, realizar-se-á a análise da experiência de videoclipe interativo desenvolvida pelo diretor Chris Milk, The Wilderness Downtown, a partir do arcabouço teórico-metodológico da sociossemiótica, em especial os regimes de interação.
Regimes of interaction in music video: The Wilderness Downtown's interactive experience
Keywords: music video; enunciative strategies; interaction; sociosemiotics; videoclipe; estratégias enunciativas; interação; sociossemiótica